Analisis Kasus Korupsi Bantuan Sosial Pada Pandemi Covid-19 dari Perspektif Etika dan Profesionalisme Hukum - Dewi, Ulva Kartika; Malik, Syaiful; Yadita, Devina; Nugraha, Rifansyah; Akbar, Soultan Raffly; Maulana, Muhammad Irfan; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research analyzes the handling of social assistance corruption cases during the COVID-19 pandemic from the perspective of legal ethics and professionalism. The research method used is normative juridical with a statutory and case approach, referring to Law Number 31 of 1999 concerning the Eradication of Corruption. The results show that social assistance corruption cases involving high-ranking officials, such as Juliari Batubara, reflect the lack of moral integrity, transparency, and accountability in the legal and governance system. The implications of this case include state financial losses, decreased public trust, and socio-economic injustice for affected communities. This research recommends strengthening technology-based monitoring mechanisms, bureaucratic reform, and increasing the role of anti-corruption institutions to restore public trust. In conclusion, strict, independent, and justice-oriented law enforcement is needed to prevent similar practices in the future.